Penerapan Sandera Pajak (Gijzeling) sebagai Instrumen Penagihan Pajak di Indonesia - Kamila, Alfina Najwa; Priyono, Joko (Law, Development and Justice Review, 2025)
This article aims to analyze the implementation of tax hostage-taking (gijzeling) as an instrument of tax collection in Indonesia. Taxes are the main source of state revenue, yet low taxpayer compliance often becomes an obstacle, leading the government to exercise its authority to enforce collection through hostage-taking. This policy has sparked controversy due to its implications for justice and law enforcement. The research questions focus on how hostage-taking is used as a coercive measure in tax debt collection and how disputes are resolved for taxpayers subjected to it. The study contributes academically to the development of tax law and practically as a reference for tax authorities and taxpayers. The method applied is normative legal research with a library approach, relying on primary and secondary legal sources, analyzed qualitatively and descriptively. The findings reveal that tax hostage-taking serves as an ultimum remedium, applicable only under specific conditions. Taxpayers may be released upon settling their tax debts and retain the right to challenge the enforcement through the District Court. Thus, tax hostage-taking functions both as a coercive compliance instrument and as a means to uphold legal certainty and justice within the taxation system.